Implementasi Media Pembelajaran Menggunakan Aplikasi Animaker untuk Meningkatkan Hasil Belajar Siswa SMK (Indo-MathEdu Intellectuals Journal, 2024)
This research has a problem formulation of how to create learning media using the Animaker application, how to apply the Animaker application as a learning media in photography material, what are the student learning outcomes in photography material using learning media based on the Animaker application, with the aim of finding out how to create learning media using animaker application, to find out how to apply the animaker application as a learning medium in photography material, to find out student learning outcomes in photography material using learning media based on the animaker application. Research that uses a quantitative approach with Quasi Experimental methods, especially the Pretest-Posttest Control Group Design. This research will be carried out at SMK PGRI Ciawigebang with research subjects of 47 class X DKV students. Data collection instruments include questionnaires and tests, as well as data analysis techniques using inferential statistics. This research aims to evaluate the effect of using Animaker learning media on student learning outcomes in photography material. The benefits of this research are expected to increase student interest and learning achievement, as well as provide knowledge and experience for researchers. From the results of hypothesis testing using the t-test, it was found that there was a significant difference in the for students